Erratum to "Eosinophils, the IL-5/IL-5Rα axis, and the biologic effects of benralizumab in severe asthma" [Respir. Med. X 1C (2019) 100007]. (2019) - Matucci, Andrea; Maggi, Enrico; Vultaggio, Alessandra
Abstract : The Publisher regrets that this article is an accidental duplication of an article that has already been published in < Respiratory Medicine: X 1C 100007>, http://dx.doi.org/<10.1016/j.yrmex.2019.100007>. The duplicate article has therefore been withdrawn. The full Elsevier Policy on Article Withdrawal can be found at https://www.elsevier.com/about/our-business/policies/article-withdrawal .